PENINGKATAN PERCAYA DIRI MELALUI MODEL PEMBELAJARAN THINK PAIR SHARE PADA SISWA SEKOLAH MINGGU BUDDHIS DI BANYUWANGI - Ariana, Titis Agnes (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2020)
This study aims to describe the implementation of the think pair share learning model in increasing students' self-confidence in Buddhist Vihara Dhamma Mukti Banyuwangi Buddhist Sunday School. Classroom action research was carried out at the Dhamma Mukti Vihara, Banyuwangi Regency. The research subjects were students of the Maha-sekha level Buddhist Sunday School (SMB) (equivalent to SMA / SMK). Data collection techniques are observation, questionnaires, and documentation. Data analysis, quantitatively, using quantitative analysis methods to determine the increase in confidence of SMB students through the think pair share learning model carried out on a Likert scale. Qualitative data analysis by describing the data either from the results of quantitative data processing or the results of observations and documentation made by researchers. The results showed that the actions taken in learning showed an increase in student confidence. Actions in this study include the use of the think pair share learning model in learning cycles 1 and 2. This increased confidence includes communication (the courage of students to ask questions, express opinions, criticize, and present discussion results), assertiveness (confident or not hesitate in conveying thinking and explaining something), self-appearance (confidence in presenting the results of the discussion), and self-control (giving full attention when learning is being done and paying attention to whoever is expressing an opinion).